2019
DOI: 10.2196/12103
|View full text |Cite
|
Sign up to set email alerts
|

Usable Mobile App for Community Education on Colorectal Cancer: Development Process and Usability Study

Abstract: Background Participation in colorectal cancer screening is still low among Malaysians despite the increasing trend of incidence, with more than half of the new cases being detected in the advanced stages. Knowledge improvement might increase screening participation and thus improve the chances of disease detection. With the advancement of communication technology, people nowadays prefer to read from their mobile phone using a Web browser or mobile apps compared with the traditional printed materia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 11 publications
1
29
0
1
Order By: Relevance
“…Our findings can be compared with usability of mobile apps as there is numerous published evidence in this area. The mean score in our study is comparable to the mean score of SKAMA (72.9 (SD ± 11.5)) which was used to assess a colorectal community education mobile app in Malaysia [38]. Other validation studies that used the original SUS had reported higher mean scores.…”
Section: Discussionsupporting
confidence: 67%
“…Our findings can be compared with usability of mobile apps as there is numerous published evidence in this area. The mean score in our study is comparable to the mean score of SKAMA (72.9 (SD ± 11.5)) which was used to assess a colorectal community education mobile app in Malaysia [38]. Other validation studies that used the original SUS had reported higher mean scores.…”
Section: Discussionsupporting
confidence: 67%
“…Most AI-powered virtual assistants provide personalized healthcare services and improve the communication between patients and care providers. In addition, AI-based applications in mobile devices, such as the Colorectal Cancer Awareness Application (ColorApp), may be used to improve community education and participation in CRC screening programs [170].…”
Section: Solutions Limitations and Future Directionsmentioning
confidence: 99%
“…The SKAMA questionnaire was readily translated, cross-culturally adapted and validated (CVI: 0.91; FVI: 0.94; Cronbach Alpha: 0.85) [ 65 ]. SKAMA has been used to assess the usability of mHealth application for community education [ 67 ]. It consisted of a 10-item survey rated from 1 (strongly disagree) to 5 (strongly agree) on a 5-point Likert scale, providing an overall subjective assessment of a system.…”
Section: Methodsmentioning
confidence: 99%